The Influence of Supportive Management on Service Delivery in Commercial Banks in Northern Kenya. - Abdikadir, Ahmed Adan; Sabwami , Butali Peter Sab; Ng’ang’a, Irura Stephen (Human Resource and Leadership Journal, 2025)
Purpose: This study investigated the relationship between supportive management and service delivery in commercial banks in Northern Kenya. Drawing on Self-Determination Theory and Social Exchange Theory. Methodology: The study employed a convergent parallel mixed-methods design, targeting 221 employees across 30 commercial bank branches. A sample of 141 front-line employees participate. Stratified sampling technique was used to select respondents proportionally. Collected data was analysed using both descriptive statistics and inferential statistics. The results will be presented in the form of figures, tables and percentages. Data collected through structured questionnaires and interview guide including 18 branch managers that provided qualitative insights via interviews. Findings: Descriptive statistics indicated a high perception of supportive management (aggregate mean 4.47) and service delivery (mean 4.69). Correlation analysis revealed a strong positive relationship between supportive management and service delivery (r = 0.796; p = .000). Regression analysis confirmed that supportive management is a consistent and significant predictor of service delivery (β = 0.371, p = 0.000). The findings emphasize the critical role of supportive management and the importance of firm-level resources in enhancing service quality in the unique Northern Kenya banking context. Unique contribution to theory, practice and policy: These study contribute new evidence on service delivery and Supportive management literature, especially within the context of unique and marginalized regions like Northern Kenya. Theoretically it supports Social exchange theory, emphasizing reciprocity. When organization provide necessary support, resources, and rewards, employee feel obliged and reciprocate with loyalty and increased efforts in turn enhance service delivery. Practically, within banking industry, prioritize leadership development programs that foster coaching, mentorship, and transparent and open communication, while also tailoring engagement practices to bank size. Policy-wise, bank regulators and CBK could develop policy and its guideline on modalities of supportive management and leadership development policy to promote and enhance employee engagement and retention of managers